Forests in post-conflict Democratic Republic of Congo: analysis of a priority agenda - Debroux, L.; Hart, T.; Kaimowitz, D.; Karsenty, A.; Topa, G. (CIFOR, The World Bank, CIRAD, 2007)
Forests are ubiquitous in the Democratic Republic of Congo; they touch the cultural and economic life of most of the population and have enormous global environmental significance. After years of conflicts and mismanagement, reconstruction is key to improving living conditions and consolidating peace. At the same time, better roads and trade bring risks—threatening forests and biodiversity by facilitating logging, land conversion, and the seizure of forest rights by vested interests. Anticipating these threats, in 2002, the transitional government started a Priority Reform Agenda. This report analyses the soundness of this Agenda, the progress achieved to date, and the priorities for the future. It emphasises the nature of forests as a public good; and the importance of the rule of law, transparency and public participation in managing natural resources. It highlights the multiplicity of claims on forests; calls for multipurpose participatory land-use planning; and emphasises the need to secure traditional user rights. Beyond the risks, the return of peace to the DRC also offers a unique opportunity to take a fresh look at the second-largest rainforest in the world, and to implement innovative strategies that give priority to the environment and to local people.